2024
DOI: 10.1186/s40001-024-01736-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index and in-stent restenosis in patients with acute coronary syndrome: a single-center retrospective study

Feng Xie,
Zuozhong Yu,
Yurong Xiong
et al.

Abstract: Background In-stent restenosis (ISR) has been shown to be correlated with inflammation. This study aimed to examine the relationship between systemic immune-inflammation index (SII, an innovative inflammatory biomarker) and ISR in acute coronary syndrome (ACS) patients after drug-eluting stent (DES) implantation. Methods Subjects who were diagnosed with ACS and underwent DES implantation were enrolled retrospectively. All individuals underwent foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…6 , 7 , 37 , 38 Two recent studies on the relationship between SII and ISR suggest that SII is independently associated with an increased risk of ISR after PCI in patients with acute coronary syndrome and may serve as an independent predictive indicator of ISR. 19 , 20 In our study, we found a strong association between high SIRI and SII levels and ISR, further confirming the possible link between systemic inflammation and the occurrence and development of ISR. We hypothesize that SIRI and SII may trigger inflammation and oxidative stress, leading to endothelial dysfunction and subsequent ISR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…6 , 7 , 37 , 38 Two recent studies on the relationship between SII and ISR suggest that SII is independently associated with an increased risk of ISR after PCI in patients with acute coronary syndrome and may serve as an independent predictive indicator of ISR. 19 , 20 In our study, we found a strong association between high SIRI and SII levels and ISR, further confirming the possible link between systemic inflammation and the occurrence and development of ISR. We hypothesize that SIRI and SII may trigger inflammation and oxidative stress, leading to endothelial dysfunction and subsequent ISR.…”
Section: Discussionsupporting
confidence: 83%
“…Two recent studies have shown that a higher SII is independently associated with an increased risk of ISR after PCI in patients with acute coronary syndrome, and may be a predictive indicator of ISR. 19 , 20 There is still a lack of effective evidence for the association between SIRI and ISR. The aim of this study was to investigate the associations of SIRI and SII with ISR in patients with coronary artery disease undergoing PCI and to evaluate the predictive value of these two indicators for ISR.…”
Section: Introductionmentioning
confidence: 99%